Perspectivas avaliativas mediadas por tecnologias: um mapeamento sistemático - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Starting from the need for a greater discussion on the thematic evaluation of learning mediated by Digital Technologies (DT) in Higher Education, more specifically in teacher training courses, it was listed as a research problem: how the publications available in the Catalog of Theses and CAPES dissertations (2015-2022) present and discuss the evaluation of technology-mediated learning? The purpose of presenting the systematic mapping of the Catalog of Theses and Dissertations of CAPES (2015-2022) and identifying the evaluative perspectives mediated by technologies in the initial training of teachers was traced.The theoretical framework addresses the concept of learning assessment, going through the different types of assessment (diagnostic, formative, classificatory), online assessment and evaluative instruments for online learning, anchored in authors such as Latchem (2014), Passerino (2010) and Valente (2018). Methodologically, it is characterized in terms of nature as qualitative, according to Yin (2016) and Minayo (2010), in terms of objectives, it is explanatory according to Gil (2010) and in terms of procedures, it is systematic mapping (MS) according to Fiorentini, Passos, de Lima (2016). The survey of empirical data was obtained in the Catalog of Theses and Dissertations of CAPES, from the insertion of the Boolean “AND” together with the descriptors that deal with the theme, namely: "digital technologies" and "learning evaluation" and " degree", based on the inclusion and exclusion criteria. Empirical data were built based on Bardin (2011) through Content Analysis, structured in three phases described as: pre-analysis with the execution of the protocol and constitution of the sample, exploration of the material that occurred by the emergence of key categories, defined a priori: (I) technological resources, (II) evaluative strategies and (III) conception of learning evaluation and treatment of results, interpretation of data supported by the theoretical framework. Among the results obtained, 43 technologies identified in the 10 analyzed works that make up the sample stand out, three of which were created and used to assess student learning in online environments. The results also point to the possibility of using these in a formative assessment. It is considered that this research can contribute to the discussions about the evaluation of learning and the use of technologies in teacher training, as it signals the importance of using these tools and creating online environments that allow the monitoring of students' learning.
Keywords: Avaliação da aprendizagem; Avaliação online; Tecnologias digitais; Learning assessment; Online assessment; Digital technologies; CNPQ::CIENCIAS HUMANAS